Ambulance use for 'primary care' problems: an ethnographic study of seeking and providing help in a UK ambulance service. Issue 10 (10th October 2019) - Booker, Matthew James; Purdy, Sarah; Barnes, Rebecca; Shaw, Ali R G
Abstract : Objectives: To explore what factors shape a service user's decision to call an emergency ambulance for a 'primary care sensitive' condition (PCSC), including contextual factors. Additionally, to understand the function and purpose of ambulance care from the perspective of service users, and the role health professionals may play in influencing demand for ambulances in PCSCs. Design: An ethnographic study set in one UK ambulance service. Patient cases were recruited upon receipt of ambulance treatment for a situation potentially manageable in primary care, as determined by a primary care clinician accompanying emergency medical services (EMS) crews. Methods used included: structured observations of treatment episodes; in-depth interviews with patients, relatives and carers and their GPs; purposeful conversations with ambulance clinicians; analysis of routine healthcare records; analysis of the original EMS 'emergency' telephone call recording. Results: We analysed 170 qualitative data items across 50 cases. Three cross-cutting concepts emerged as central to EMS use for a PCSC: (1) There exists a typology of nine 'triggers', which we categorise as either 'internal' or 'external', depending on how much control the caller feels they have of the situation; (2) Calling an ambulance on behalf of someone else creates a specific anxiety about urgency; (3) Healthcare professionals experience conflict around fuelling demand for ambulances. Conclusions: Previous work suggests a range of sociodemographic factors that may be associated with choosing ambulance care in preference to alternatives. Building on established sociological models, this work helps understand how candidacy is displayed during the negotiation of eligibility for ambulance care. Seeking urgent assistance on behalf of another often requires specific support and different strategies. Use of EMS for such problems—although inefficient—is often conceptualised as 'rational' by service users. Public health strategies that seek to advise the public about appropriate use of EMS need to consider how individuals conceptualise an 'emergency' situation.